2007
DOI: 10.1002/pd.1744
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal demonstration of afferent vessels and progressive thrombosis in a torcular malformation

Abstract: The vascular malformation had a fixed volume and preceded the thrombosis, which formed within several days. The present case is the first report with all the prenatal sonographic features of this condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 15 publications
0
13
0
2
Order By: Relevance
“…There are about 40 cases of prenatally diagnosed thrombosis of the torcular herophili in the literature (case reports [3][4][5][6][7][8][9][10] and case series [11][12][13][14][15][16] ). We present a series of eight cases, the largest single-center series yet reported.…”
Section: Introductionmentioning
confidence: 99%
“…There are about 40 cases of prenatally diagnosed thrombosis of the torcular herophili in the literature (case reports [3][4][5][6][7][8][9][10] and case series [11][12][13][14][15][16] ). We present a series of eight cases, the largest single-center series yet reported.…”
Section: Introductionmentioning
confidence: 99%
“…Termination of pregnancy took place in 7 of 22 cases, of which in 4 cases the prognosis was unpredictable; in one case, sonography showed enlargement of the mass and the surrounding fluid with increased compression on the posterior fossa and the brain system, 5 and in the fifth case, color Doppler imaging revealed vascular flow within this lesion 8 . One infant died postnatally after surgical management, and another died in the fourth postnatal month; in that case, a painful lambdoid tumor was diagnosed.…”
mentioning
confidence: 99%
“…In addition, Grange et al 5 recently reported progressive formation of a thrombus in a dilated torcular. The authors concluded that a primary venous malformation led to aberrant flow and progressive clot formation.…”
mentioning
confidence: 99%
“…Several authors have published their experience in using magnetic resonance imaging (MRI) to aid in the diagnosis. [1][2][3][4][5][6][7] We describe how dedicated 2-dimensional (2D)/3-dimensional (3D) neurosonography with power Doppler imaging accurately diagnosed this lesion in the third trimester. In addition, we present the findings of the pathologist's examination, which may shed light on the pathophysiologic mechanisms of this lesion.…”
mentioning
confidence: 99%
See 1 more Smart Citation